Preparation method of high-toughness NDI-based fluorescent polyurea
By introducing NDI-based fluorescent polyurea into the polyurea material, the gradient energy dissipation and naphthalene ring structure are used to solve the challenges of polyurea materials in taking into account high toughness and fluorescence characteristics, achieving both high toughness and fluorescence of the material, and having responsiveness to stretching and acid-base environments.
Patent Information
- Application Number
- CN202411790896.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing polyurea materials have challenges in taking into account high toughness and fluorescence characteristics, and are difficult to be widely used in some fields.
By introducing NDI-based fluorescent polyurea, gradient energy dissipation is formed by using the difference between hydrogen bonds and covalent bond fracture energy, which enhances the toughness of the material, and imparts the fluorescence characteristics of the material through the introduction of a planar rigid conjugated structure (naphthalene ring).
The high toughness and fluorescence characteristics are achieved, the material is responsive in stretching and acid-base environments, and the fluorescence intensity can be adjusted by changing the degree of crosslinking and substituents on the naphthalene ring.
Smart Images

Figure CN119591833A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer preparation, and particularly relates to a method for preparing high-toughness NDI (1,5-naphthalene diisocyanate)-based fluorescent polyurea. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Polyurea is a polymer material produced by the step-by-step addition reaction of isocyanate components and amino compound components. No by-products are produced during the reaction, and it often has good mechanical properties. It is widely used in pipeline anti-corrosion, surface decoration and other fields. Nowadays, the isocyanate components used in the synthesis of polyurea are usually IPDI (isophorone diisocyanate), HDI (hexamethylene diisocyanate), TDI (toluene diisocyanate) and MDI (diphenylmethane diisocyanate). The application of NDI (naphthalene diisocyanate) in the field of polyurea is very rare. This is mainly due to the high melting point of NDI, and the temperature must be above 120°C for the melting reaction to proceed. The amino group and isocyanate react too violently at high temperatures and cannot be polymerized normally, which makes this method unable to be applied in the field of polyurea. However, the highly symmetrical structure and rigidity of NDI give it good physical and chemical properties, and its application in the field of polyurea has a very broad application prospect.
[0004] Cross-linked polyurea materials are polymers with a three-dimensional network structure formed by chemical or physical cross-linking. Due to their unique structure, cross-linked polyurea materials usually have high hardness and rigidity, and exhibit excellent mechanical properties and chemical resistance in many applications. However, these materials also have some inherent disadvantages. Due to the cross-linking between chains, the chain mobility is reduced and the toughness is often poor, which limits their wide application in some fields.
[0005] The fluorescence of organic polymer materials is mainly caused by the structure of molecules in a certain area in the chain segment or between the chain segments. Its photoluminescence performance mainly depends on the conjugated structure, the interaction between molecules and molecules, which mainly includes π-π interaction, hydrogen bond and halogen bond, etc. Due to its special luminescence properties, fluorescence can be applied in many fields, such as information storage and encryption, information marking and display, etc. However, current polyurea products often have difficulty in achieving both high toughness and fluorescence properties. Summary of the invention
[0006] In order to solve the above problems, the present invention provides a high-toughness NDI-based fluorescent polyurea and a preparation method thereof. Based on the difference in the breaking energy of hydrogen bonds and covalent bonds, a gradient energy dissipation is formed to enhance the toughness of the material, and a planar rigid large conjugated structure (naphthalene ring) is introduced to give the material fluorescent properties. The fluorescence intensity of the material can be changed by changing the cross-linking degree of the material and the substituents on the naphthalene ring, and it has a certain response to stretching and acid-base.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] In a first aspect of the present invention, a high-toughness NDI-based fluorescent polyurea is provided, the structural formula of which is as follows:
[0009]
[0010] Wherein, n is a natural number greater than zero.
[0011] The high-toughness NDI-based fluorescent polyurea system of the present invention contains a naphthalene ring. When the substituent on the naphthalene ring is a urea group and the system is composed entirely of urea groups, the fluorescence intensity is maximum. When the substituent on the naphthalene ring is a carbamate and the system is composed entirely of carbamate bonds, the fluorescence intensity is minimum.
[0012] The second aspect of the present invention provides a method for preparing a high-toughness NDI-based fluorescent polyurea, comprising:
[0013] The NDI is reacted with a polyetheramine to obtain an isocyanate-terminated prepolymer;
[0014] The isocyanate-terminated prepolymer is chain extended by using TEPA, and after the reaction is completed, diisocyanate is added to continue the reaction to obtain the product.
[0015] Under the action of external force, the gradual breaking of interactions at different levels can greatly dissipate energy, thus making the material have excellent toughness. Therefore, the present invention introduces different levels of hydrogen bonds and covalent bonds into the polyurea network to form gradient energy dissipation, thereby enhancing the toughness of the material. The prepared NDI-based fluorescent polyurea takes into account both mechanical strength and toughness, and can meet the use requirements of different fields.
[0016] In some embodiments, the molar ratio of NDI to polyetheramine is 1:0.3-1.
[0017] When reacting in a solvent at a temperature above 60°C, NDI will undergo many side reactions, such as reacting with water, DMF, etc. Therefore, the present invention utilizes the high reactivity of amino groups with isocyanates to allow them to react under milder conditions. Preferably, the temperature for the reaction of NDI with polyetheramine is 0°C-60°C.
[0018] In some embodiments, the temperature of the chain extension reaction is room temperature.
[0019] In some embodiments, the molar ratio of the polyetheramine to TEPA is 1:0.3-1.
[0020] In some embodiments, the reaction temperature of diisocyanate and secondary amine is 50-100°C.
[0021] In some embodiments, the molar ratio of TEPA to diisocyanate is 1:0.3-1.6.
[0022] In some embodiments, the diisocyanate is selected from one of IPDI, HDI, and TDI.
[0023] The third aspect of the present invention provides the application of the above-mentioned high-toughness NDI-based fluorescent polyurea in the fields of information storage and encryption, information marking and display.
[0024] Beneficial Effects of the Invention
[0025] (1) The preparation method of the high-toughness NDI-based fluorescent polyurea described in the present invention is novel, the conditions are mild, and it has profound research value.
[0026] (2) The present invention is based on a gradient energy dissipation mechanism, which utilizes the breaking of strong and weak hydrogen bonds in the material and the breaking of side chain covalent bonds to form a gradient energy dissipation, thereby reducing stress concentration. As the stretching proceeds, the breaking of side chain covalent bonds will produce new hydrogen bond donors and acceptors, which is beneficial to the rapid recombination of hydrogen bonds, further enhancing the energy dissipation mechanism, and promoting the slippage and rearrangement of chain segments, thereby giving the material ultra-high toughness.
[0027] (3) The present invention imparts fluorescent properties to the material by introducing a planar rigid conjugated structure (naphthalene ring), restricts the "movement" of the naphthalene ring through cross-linking between the main chains, and enhances the fluorescent properties of the material, and the acid and alkali can change the fluorescence intensity of the material. By changing the type of substituents on the naphthalene ring, the fluorescent properties have obvious changes.
[0028] (4) The preparation method of the present invention is simple, inexpensive, highly practical, and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention, and the exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute improper limitations on the present invention.
[0030] Figure 1 This is a graph showing the toughness of polyurea with different crosslinking degrees.
[0031] Figure 2 This is the fluorescence spectrum of polyurea with the same cross-linking degree.
[0032] Figure 3 The fluorescence spectra of NDI-based fluorescent polyurea at different pH values.
[0033] Figure 4 The fluorescence spectra of different substituents on the naphthalene ring. DETAILED DESCRIPTION
[0034] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0035] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.
[0036] In the following examples, the following test methods were used:
[0037] The tensile test was carried out according to the national standard GB / T1024.2-2006, with a test speed of 100 mm / min and at room temperature.
[0038] Fluorescence spectra were measured under unified standards.
[0039] Embodiment 1:
[0040] Using DMAC as solvent, add polyetheramine D-2000 (10 g) and NDI (1.576 g) into a 250 ml three-necked flask and heat at 50 °C and N 2 In the atmosphere, the reaction was continued until the solid completely disappeared to obtain a viscous solution, which was the prepolymer. After cooling to room temperature, TEPA (0.473 g) was dissolved in DMAC and added to the prepolymer. During the period, solvent was continuously added to dilute to prevent gelation. The reaction was continued at room temperature for 3 hours. After the reaction was completed, IPDI (0.305 g) was added to the three-necked flask and the reaction was continued at 65°C for 7 hours. After the reaction was completed, a viscous polyurea DMAC solution was obtained, which was poured into a mold and dried at 70°C to form a film.
[0041] Embodiment 2:
[0042] Using DMAC as solvent, add polyetheramine D-2000 (10 g) and NDI (1.576 g) into a 250 ml three-necked flask and heat at 50 °C and N 2In the atmosphere, the reaction was continued until the solid completely disappeared to obtain a viscous solution, which was the prepolymer. After cooling to room temperature, TEPA (0.473 g) was dissolved in DMAC and added to the prepolymer. During the period, solvent was continuously added to dilute to prevent gelation. The reaction was continued at room temperature for 3 hours. After the reaction was completed, IPDI (0.611 g) was added to the three-necked flask and the reaction was continued at 65°C for 7 hours. After the reaction was completed, a viscous polyurea DMAC solution was obtained, which was poured into a mold and dried at 70°C to form a film.
[0043] Embodiment 3:
[0044] Using DMAC as solvent, add polyetheramine D-2000 (10 g) and NDI (1.576 g) into a 250 ml three-necked flask and heat at 50 °C and N 2 In the atmosphere, the reaction was continued until the solid completely disappeared to obtain a viscous solution, which was the prepolymer. After cooling to room temperature, TEPA (0.473 g) was dissolved in DMAC and added to the prepolymer. During the period, solvent was continuously added to dilute to prevent gelation. The reaction was continued at room temperature for 3 hours. After the reaction was completed, IPDI (0.917 g) was added to the three-necked flask and the reaction was continued at 65°C for 7 hours. After the reaction was completed, a viscous polyurea DMAC solution was obtained, which was poured into a mold and dried at 70°C to form a film.
[0045] Embodiment 4:
[0046] Using DMAC as solvent, add polyetheramine D-2000 (10 g) and NDI (1.576 g) into a 250 ml three-necked flask and heat at 50 °C and N 2 In the atmosphere, the reaction was continued until the solid completely disappeared to obtain a viscous solution, which was the prepolymer. After cooling to room temperature, TEPA (0.473 g) was dissolved in DMAC and added to the prepolymer. During the period, solvent was continuously added to dilute to prevent gelation. The reaction was continued at room temperature for 3 hours. After the reaction was completed, HDI (0.694 g) was added to the three-necked flask and the reaction was continued at 65°C for 7 hours. After the reaction was completed, a viscous polyurea DMAC solution was obtained, which was poured into a mold and dried at 70°C to form a film.
[0047] Embodiment 5:
[0048] Using DMAC as solvent, add polyetheramine D-2000 (10 g) and NDI (1.576 g) into a 250 ml three-necked flask and heat at 50 °C and N 2In the atmosphere, the reaction was continued until the solid completely disappeared to obtain a viscous solution, which was the prepolymer. After cooling to room temperature, TEPA (0.473 g) was dissolved in DMAC and added to the prepolymer. During the period, solvent was continuously added to dilute to prevent gelation. The reaction was continued at room temperature for 3 hours. After the reaction was completed, TDI (0.718 g) was added to the three-necked flask and the reaction was continued at 65°C for 7 hours. After the reaction was completed, a viscous DMAC solution of polyurea was obtained, which was poured into a mold and dried at 70°C to form a film.
[0049] Comparative Example 1:
[0050] Using DMAC as solvent, add polyetheramine D-2000 (10 g) and NDI (1.576 g) into a 250 ml three-necked flask and heat at 50 °C and N 2 The reaction was continued under the atmosphere until the solid completely disappeared to obtain a viscous solution, which was the prepolymer. After cooling to room temperature, TEPA (0.473 g) was dissolved in DMAC and added to the prepolymer. During this period, solvent was continuously added to dilute to prevent gelation. The reaction was continued at room temperature for 3 hours. After the reaction was completed, a viscous polyurea DMAC solution was obtained, which was poured into a mold and dried at 70°C to form a film.
[0051] Comparative Example 2:
[0052] Using DMAC as solvent, polyethylene glycol (Mn=2000, 4 g), HDI (0.706 g), and DBTDL (0.02 g) were added to a 100 ml three-necked flask and heated at 80°C and N 2 Under atmosphere, mechanical stirring was performed for 2 h to obtain a colorless viscous solution, which was the prepolymer. After obtaining the prepolymer, 1,5-dihydroxynaphthalene (0.32 g) was added and heated at 80 °C and N 2 The reaction was continued for 6 hours under the atmosphere. After the reaction was completed, a viscous polyurea DMAC solution was obtained, which was poured into a mold, dried at 70° C., and its fluorescence intensity was measured.
[0053] Comparative Example 3:
[0054] Using DMAC as solvent, polyetheramine (Mn=2000, 4 g), HDI (0.706 g), and DBTDL (0.02 g) were added to a 100 ml three-necked flask and heated at 80°C and N 2 Under atmosphere, mechanical stirring was performed for 2 h to obtain a colorless viscous solution, which was the prepolymer. After obtaining the prepolymer, 1,5-dihydroxynaphthalene (0.32 g) was added and heated at 80 °C and N 2 The reaction was continued for 6 hours under the atmosphere. After the reaction was completed, a viscous polyurea DMAC solution was obtained, which was poured into a mold, dried at 70° C., and its fluorescence intensity was measured.
[0055] Comparative Example 4:
[0056] Using DMAC as solvent, polyetheramine (Mn=2000, 4 g), HDI (0.706 g), and DBTDL (0.02 g) were added to a 100 ml three-necked flask and heated at 80°C and N 2 Under atmosphere, mechanical stirring was performed for 2 h to obtain a colorless viscous solution, which was the prepolymer. After obtaining the prepolymer, 1,5-diaminonaphthalene (0.316 g) was added and stirred at 80 °C and N 2 The reaction was continued for 6 hours under the atmosphere. After the reaction was completed, a viscous polyurea DMAC solution was obtained, which was poured into a mold, dried at 70° C., and its fluorescence intensity was measured.
[0057] (Comparative Examples 2, 3, and 4 were only analyzed for fluorescence intensity to compare the effects of substituents on the naphthalene ring on fluorescence intensity, without exploring their mechanical properties.)
[0058] As shown in Table 1, which is a comparison table of mechanical properties of different embodiments and comparative examples, it is proved that the high-toughness NDI-based fluorescent polyurea synthesized in the present invention has ultra-high toughness and excellent elongation at break.
[0059] Table 1
[0060]
[0061]
[0062] like Figure 1 As shown, NSPUA (Comparative Example 1), NSPUA-IP1 (Example 1), NSPUA-IP2 (Example 2) and NSPUA-IP3 (Example 3) respectively represent the ratio of no cross-linking agent added to the ratio of cross-linking agent added (the larger the number, the larger the ratio). As the cross-linking agent content increases, the degree of cross-linking increases and the toughness is greatly improved.
[0063] like Figure 2 As shown, with the increase of cross-linking degree, the "movement" of naphthalene ring is restricted, non-radiative transition is weakened, radiative transition is enhanced, and fluorescence intensity increases.
[0064] like Figure 3 As shown, NSPUA-IP3 (Example 3) was immersed in solutions with different pH values for 24 hours, and its fluorescence intensity was measured. It can be seen that the fluorescence intensity has changed significantly, which is because different acid-base environments change the existence form of substituents on the naphthalene ring and affect the electron cloud density of the naphthalene ring, and the fluorescence intensity of the material changes accordingly.
[0065] Figure 4As shown, NN (Comparative Example 4) represents that the system is all urea groups, NO (Comparative Example 3) represents that the substituents on the naphthalene ring are carbamate bonds, and there are urea groups in the system, and OO (Comparative Example 2) represents that the system is all carbamate bonds. The fluorescence intensity when the substituents on the naphthalene ring are urea groups and the system is all urea groups is much greater than the fluorescence intensity when there are carbamate bonds in the system. The hydrogen bond energy formed between urea groups is higher than the hydrogen bond energy between carbamate bonds, and the spacing is closer. The greater the restriction on the "activity" range of the naphthalene ring, the fewer non-radiative transitions, the enhanced radiative transitions, and the enhanced fluorescence intensity.
[0066] The above fluorescent properties make this material applicable to marking, display and other fields.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-toughness NDI-based fluorescent polyurea, characterized in that: The structural formula is as follows: Wherein, n is a natural number greater than zero.
2. A method for preparing a high-toughness NDI-based fluorescent polyurea, characterized in that: include: The NDI is reacted with a polyetheramine to obtain an isocyanate-terminated prepolymer; The isocyanate-terminated prepolymer is chain extended by using TEPA, and after the reaction is completed, diisocyanate is added to continue the reaction to obtain the product.
3. The method for preparing the high-toughness NDI-based fluorescent polyurea according to claim 2, characterized in that: The molar ratio of NDI to polyetheramine is 1:0.3-1.
4. The method for preparing the high-toughness NDI-based fluorescent polyurea according to claim 2, characterized in that: The temperature for reacting the NDI with the polyetheramine is 0°C-60°C.
5. The method for preparing high-toughness NDI-based fluorescent polyurea according to claim 2, characterized in that: The temperature of the chain extension reaction is room temperature.
6. The method for preparing high-toughness NDI-based fluorescent polyurea according to claim 2, characterized in that: The molar ratio of the polyetheramine to TEPA is 1:0.3-1.
7. The method for preparing high-toughness NDI-based fluorescent polyurea according to claim 2, characterized in that: The reaction temperature of diisocyanate and secondary amine is between 50 and 100°C.
8. The method for preparing high-toughness NDI-based fluorescent polyurea according to claim 2, characterized in that: The molar ratio of TEPA to diisocyanate is 1:0.3-1.
6.
9. The method for preparing high-toughness NDI-based fluorescent polyurea according to claim 2, characterized in that: The diisocyanate is selected from one of IPDI, HDI and TDI.
10. Application of the high-toughness NDI-based fluorescent polyurea according to claim 1 in the fields of information storage and encryption, information marking and display.
Citation Information
Patent Citations
Castable polyurea compositions for golf ball covers
CN102414235A
Reversible hydrogen bond cross-linked shape memory polyurea elastomer and preparation method thereof
CN114656612A
Fluorescent polyurea material as well as preparation method and upgrading and recycling method thereof
CN116535600A
Physical crosslinking type polyether amine elastomer containing eight hydrogen bond structure as well as preparation and application of physical crosslinking type polyether amine elastomer
CN117003988A
Cited By
Polyurea functional material with stimulation fluorescence response and preparation method thereof
CN120484227A